A Review of Pediatric Critical Care in Resource-Limited Settings: A Look at Past, Present, and Future Directions - Turner, Erin L.; Nielsen, Katie R.; Jamal, Shelina M.; von Saint André-von Arnim, Amelie; Musa, Ndidiamaka L. (Frontiers in Pediatrics, 2016)
Fifteen years ago, United Nations world leaders defined Millennium Development Goal 4 (MDG 4): to reduce under-5 year mortality rates by two-thirds by the year 2015. Unfortunately, only 27 of 138 developing countries are expected to achieve MDG 4. The majority of childhood deaths in these settings result from reversible causes, and developing effective pediatric emergency and critical care services could substantially reduce this mortality. The Ebola outbreak highlighted the fragility of health care systems in resource-limited settings and emphasized the urgent need for a paradigm shift in the global approach to healthcare delivery related to critical illness. This review provides an overview of pediatric critical care in resource-limited settings and outlines strategies to address challenges specific to these areas. Implementation of these tools has the potential to move us toward delivery of an adequate standard of critical care for all children globally, and ultimately decrease global child mortality in resource-limited settings.